Ocular gene therapy targeting retinal angiogenesis and vascular leakage: translational and clinical evidence from a systematic review and meta-analysis - Kai-Yang Chen; Hoi-Chun Chan; Chi-Ming Chan (Angiogenesis, 2026)
Introduction Retinal diseases driven by pathological angiogenesis and vascular leakage, including neovascular age-related macular degeneration and diabetic retinopathy, impose substantial visual and treatment burdens because current anti-vascular endothelial growth factor (anti-VEGF) therapy requires repeated intravitreal administration. Ocular gene therapy can provide durable intraocular expression of therapeutic proteins and sustained pathway-level disease control. Methods This systematic review and meta-analysis was prospectively registered in the International Prospective Register of Systematic Reviews (PROSPERO) and conducted according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) 2020 guidelines. PubMed, Scopus, Web of Science, ScienceDirect, and the Cochrane Library were searched from inception to April 21, 2026. Eligible studies included preclinical, in vitro, and clinical investigations of gene-based interventions targeting retinal angiogenesis, vascular permeability, or related anatomical and treatment-burden outcomes. Random-effects meta-analyses were performed using standardized mean differences (SMDs), mean differences (MDs), and logit event rates. Results Twenty-five studies were included. Preclinical gene therapy significantly reduced pathological neovascularization, with a pooled standardized mean difference (SMD) of −1.16 (95% confidence interval [CI], −1.48 to −0.84; p < 0.001) and negligible heterogeneity (I² = 0%). Vascular leakage was also significantly reduced across preclinical experimental studies, with a pooled mean difference (MD) of 0.215 (95% CI, 0.178–0.251; p < 0.001; I 2 = 0%) after directional harmonization. In clinical cohorts, ocular gene therapy significantly reduced central subfield thickness (CST) by −55.30 μm (95% CI, −72.58 to −38.03; p < 0.001) and was associated with reduced anti-vascular endothelial growth factor (anti-VEGF) treatment burden, with a pooled logit event rate of 0.62 (95% CI, 0.20–1.04; p = 0.0039), corresponding to a pooled proportion of approximately 65% of participants meeting study-specific criteria for reduced supplemental anti-VEGF use. Conclusion Ocular gene therapy shows strong preclinical anti-angiogenic and anti-permeability effects, with emerging clinical evidence of anatomical improvement and reduced anti-VEGF treatment burden in neovascular retinal disease cohorts. Larger disease-specific randomized trials are required to confirm long-term efficacy, safety, and patient selection.